LAKE WATER QUALITY ASSESSMENT IN UNIVERSITI SELANGOR BESTARI JAYA CAMPUS: A PRELIMINARY STUDY - Noor Halini Baharim; Tuan Azmar Tuan Daud; Hanita Hashim; Noor Fazreen Dzulkafli (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
Water quality study on the main lake of Universiti Selangor (UNISEL) Bestari Jaya Campus was conducted on weekly basis for twelve weeks. The level of pollution in the lake was classified according to Interim National Water Quality Standard (INWQS) and Water Quality Index (WQI). Three sampling stations were chosen and the concentration of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS) and Ammonia-Nitrogen (AN) were determined. Water samples were analyzed physically and chemically. The physical water quality parameter, Dissolved Oxygen (DO), temperature and pH were measured in situ and the chemical parameter of BOD, COD, TSS and AN were analyzed in the laboratory according to the APHA Method. Throughout the study period, the water temperature was recorded in the range of 28.0 oC to 29.1 oC and pH of the water was recorded at neutral level. Based on INWQS, COD, TSS, pH and AN parameters were classified in Class II. DO parameter was classified in Class III which indicate that the lake was slightly polluted and BOD parameter was classified Class V which is heavily polluted. Analysis of water parameter according to WQI showed the main lake was classified in Class IV. Based on these two water quality standards, this can be concluded that the main lake in UNISEL Bestari Jaya Campus were polluted and further actions need to be taken by the management of the university in order the improved the water quality of the lake.